1998
DOI: 10.1046/j.1365-3040.1998.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of leaf versus whole plant CO2 environment for photosynthetic acclimation

Abstract: , unloading of the phloem at the sinks, or utilization for growth of sinks. To determine the relative importance of leaf versus whole plant level limitations on carbohydrate utilization at elevated CO 2 , and the possible effects on the regulation of photosynthetic capacity, we constructed a treatment system in which we could expose single, attached, soybean leaflets to CO 2 concentrations different from those experienced by the rest of the plant. The single leaflet treatments had dramatic effects on the carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 52 publications
1
33
3
Order By: Relevance
“…Experiments about the response of single, attached leaflets of soybean exposed to different CO 2 concentrations independently of the whole plant, showed strong effects on the carbohydrate content of the leaflets (Sims et al, 1998). However, the authors found that photosynthetic capacity and Rubisco content were unaffected by the individual leaflet treatment and instead was regulated on the whole plant level.…”
Section: Article In Pressmentioning
confidence: 97%
“…Experiments about the response of single, attached leaflets of soybean exposed to different CO 2 concentrations independently of the whole plant, showed strong effects on the carbohydrate content of the leaflets (Sims et al, 1998). However, the authors found that photosynthetic capacity and Rubisco content were unaffected by the individual leaflet treatment and instead was regulated on the whole plant level.…”
Section: Article In Pressmentioning
confidence: 97%
“…These evidences strongly support our argument that downregulation of Rubisco at elevated p(CO 2 ) are not due to reduced Rubisco synthesis. In addition, an elegant work by Sims et al (1998) had demonstrated that when a soybean leaflet was exposed to elevated p(CO 2 ) while the rest of the plant was exposed to ambient p(CO 2 ), there was a dramatic effect on the soluble carbohydrate accumulation but Rubisco content remained unchanged in the single leaflet. On the other hand, when the rest of the plant was exposed to elevated p(CO 2 ) and a single leaflet exposed to …”
Section: Rubisco Turnover At Elevated P(co 2 )mentioning
confidence: 99%
“…Remarkably, this is not a cell-autonomous response but is controlled at the whole plant level (148). Phytohormones, like ABA, may mediate such systemic responses.…”
Section: Abscisic Acid and Gibberellic Acidmentioning
confidence: 99%